CONNECTED HOME: SNOW MELTING ANALYSIS FOR THE CITY OF ASTANA - Savig, Josiah Stuart; Orynbassarova, Nazym; Kamzabek, Dana (Nazarbayev University, Graduate School of Business, 2022)
With the unpredictability of weather conditions increasing in recent decades, colder densely populated areas around the world are struggling to keep up with the demand to keep their cities clean, businesses operating, and citizens safe during periods of heavy snowfall. Many developed urban centers rely on a system of hauling snow outside city limits, though many have been incorporating or switching entirely to snow melting machines to better meet residents’ needs. Through data provided by Connected Home and BI Group and our own research and analysis, we have found that the implementation of certain snow melting machines may prove to be both economically and ecologically beneficial, along with alleviating street traffic congestion.
Keywords: Type of access: Restricted; snow melting; Astana